Whole Atmosphere Simulation of Anthropogenic Climate Change. Issue 3 (10th February 2018) - Solomon, Stanley C.; Liu, Han‐Li; Marsh, Daniel R.; McInerney, Joseph M.; Qian, Liying; Vitt, Francis M.
Abstract: We simulated anthropogenic global change through the entire atmosphere, including the thermosphere and ionosphere, using the Whole Atmosphere Community Climate Model‐eXtended. The basic result was that even as the lower atmosphere gradually warms, the upper atmosphere rapidly cools. The simulations employed constant low solar activity conditions, to remove the effects of variable solar and geomagnetic activity. Global mean annual mean temperature increased at a rate of +0.2 K/decade at the surface and +0.4 K/decade in the upper troposphere but decreased by about −1 K/decade in the stratosphere‐mesosphere and −2.8 K/decade in the thermosphere. Near the mesopause, temperature decreases were small compared to the interannual variation, so trends in that region are uncertain. Results were similar to previous modeling confined to specific atmospheric levels and compared favorably with available measurements. These simulations demonstrate the ability of a single comprehensive numerical model to characterize global change throughout the atmosphere. Plain Language Summary: We performed the first whole‐atmosphere simulations of global change that include the lower atmosphere (0–15 km), middle atmosphere (15–90 km), and thermosphere‐ionosphere (90–500 km). All significant known changes caused by human activity were included in a new version of the Whole Atmosphere Community Climate Model‐eXtended. The basic result is that even as the lower atmosphere gradually warms, the upper atmosphere rapidly cools. Simulations were conducted using constant low solar activity conditions, in order to remove the effects of the solar cycle on the upper atmosphere. Global mean annual average temperature increased at a rate of +0.2 K/decade at the surface and +0.4 K/decade about 10 km above the surface but decreased throughout the upper atmosphere, from about 20 km to 500 km, reaching −2.8 K/decade above 200 km. Near 90 km, very small temperature decreases were calculated, but the year‐to‐year variation was large, so temperature trends in that altitude region are uncertain. Results were similar to those obtained from previous work using numerical models that were confined to specific atmospheric levels and compare favorably with available measurements. These simulations demonstrate the ability of a single comprehensive numerical model to characterize global change throughout the atmosphere. Key Points: We have performed the first comprehensive whole‐atmosphere climate change simulations, including the thermosphere and ionosphere Results for solar minimum conditions indicate slow warming in the troposphere, changing to rapid cooling in the upper atmosphere In the mesopause region, systematic change was very small but exhibited considerable interannual variability